Розробка методів розрахунку елементів конструкцій із в'язкопружних композиційних матеріалів - Мартиненко, Володимир Геннадійович (НТУ "ХПІ", 2018)
Дисертація на здобуття наукового ступеня кандидата технічних наук за спеціальністю 05.02.09 – динаміка та міцність машин. Національний технічний університет "Харківський політехнічний інститут", Харків, 2018 р. Дисертацію присвячено створенню нових методів опису та моделювання анізотропної в'язкопружності композиційних елементів конструкцій і машин. На підставі аналізу актуальних методик встановлено, що на даний момент не існує комплексного підходу до встановлення параметрів анізотропної в'язкопружності полімерних армованих композиційних матеріалів, а також моделювання їхньої механічної поведінки. З метою визначення властивостей в'язкопружного композиту був розроблений чисельний метод гомогенізації ядер ортотропної в'язкопружності ортогонально армованого композиційного матеріалу. Спланований та реалізований експеримент зі знаходження параметрів анізотропної в'язкопружності склотекстоліту кількісно та якісно підтвердив результати чисельних розрахунків, що продемонструвало необхідність врахування в'язкопружних властивостей із загальним ступенем анізотропії при моделюванні механіки елементів конструкцій і машин, виконаних із полімерних армованих композиційних матеріалів. Запропонований в роботі метод накладених сіток надав до цього моменту відсутні можливості моделювання будь якого ступеня анізотропії в'язкопружних властивостей в програмних комплексах скінченно-елементного. Цей метод в роботі був застосований до моделювання контакту ділянки пружного трубопроводу із ортотропним в'язкопружним ремонтним бандажем за допомогою тривимірної в'язкопружної скінченно-елементної моделі, що в порівнянні із розробленими аналітичною та чисельно-аналітичною моделями плоского вісесиметричного напружено-деформованого стану такої конструкції показало його адекватність та високу точність.

Thesis for granting the Degree of Candidate of Technical sciences in speciality 05.02.09 – Dynamics and Strength of Machines. – National Technical University "Kharkiv Politechnical Institute", 2018. The thesis is dedicated to a creation of new methods for describing and modeling the anisotropic viscoelasticity of composite structural elements. Basing on an analysis of actual methods it is established that at the moment there is no a complex approach for determining anisotropic viscoelastic parameters of polymer reinforced composite materials and modeling their mechanical behavior. With a purpose of finding the quantitative and qualitative properties of a viscoelastic composite, a numerical method for homogenizing orthotropic viscoelastic kernels of orthogonally reinforced composite material, that are dependent on a fiber volume fraction, time and temperature, was developed. The time dependencies of these kernels were approximated by Prony series, whereas the temperature ones were approximated by Williams-Landel-Ferry shift function. This approach allowed to indicate that the viscoelasticity of fiber reinforced polymeric composite materials is of orthotropic nature for an orthogonal reinforcement scheme, that the relaxation curves of viscoelastic parameters are not similar to each other, which contradicts the classical engineering viscoelastic models, and that the temperature dependency of these properties coincide with the ones of the composite polymeric matrix. The planned and realized experiment on finding the parameters of anisotropic viscoelasticity of a fiber-glass with a woven reinforcement scheme has confirmed the results of numerical calculations, which demonstrated the need to take into account viscoelastic properties with a general degree of anisotropy when modeling the mechanics of structural elements and machines made of fiber reinforced polymeric composite materials. The experiment rig was improved during the research in order to satisfy the requirements for carrying out tests on plane polymeric composite samples. The method of super-imposed meshes proposed in the work provided the possibilities of modeling any degree of anisotropy of viscoelastic properties in commercial finite-element codes without a necessity to create additional material user subroutines using only the standard tools of these codes. The convergence of the method was also proved in the work. This method was applied to modeling a contact behavior of an elastic pipeline section with an orthotropic viscoelastic repair bandage using a three-dimensional viscoelastic finite element model that in comparison with the developed analytical and numerical-analytical models of a plane axisymmetric stress-strain state of such a design showed its adequacy and accuracy. In addition, proposed analytical and numerical-analytical methods allowed to take into account mounting features of repair band-age assembled on unloaded or loaded pipeline with or without tension, that enabled to indicate a relaxation of contact stresses for different repair regimes.
Development of methods for calculation of constructional elements of viscoelastic composite materials
Keywords: конструкційна міцність; статичне навантаження; експериментальний метод; анізотропна в'язкопружність; композиційний матеріал; ряд Проні; зсувна функція; апроксимація; структурний метод; ремонтний бандаж; контактна задача; аналітична модель; чисельно-аналітичний метод; метод скінченних елементів; автореферат дисертації; structural strength; static load; experimental method; anisotropic viscoelasticity; composite material; thermorheologically simple material; Prony series; shift function; approximation; structural method; repair bandage; contact problem; analytical model; numerical-analytical method; finite-element method; 539.376